Periodic poling with short period for thin film lithium niobate waveguides - Younesi, Mohammadreza; Kumar, Pawan; Stanicki, Badrudin Jakob; Geiss, Reinhard; Chang, Wei Kun; Chen, Yen Hung; Setzpfandt, Frank; Pertsch, Thomas (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Lithium niobate (LN) is a favourable material for many applications, especially in integrated optics, due to its excellent electro-optic, acousto-optic, and nonlinear optic properties. One promising application of LN is second-harmonic generation (SHG). For enhancing the efficiency of SHG, phase matching between the interacting waves is needed, which is often realized by employing quasi-phase matching (QPM) [1]. QPM is typically realized by periodic poling of LN [2,3], i.e. the periodic flipping of the crystal orientation. The needed period is determined by the wavelengths as well as by the wave vectors of the fundamental- and the second-harmonic waves (FW and SH, respectively). For the case of backward SHG with a fundamental wavelength of 1.55 μm, where the SH wave travels in the opposite direction to the FW, typically sub-micrometer periods of the poled LN are required [4].
CRIS-Team Scopus Importer:2023-04-20